Age at injury is associated with the long-term cognitive outcome of traumatic brain injuries - Li, Wei (Alzheimers Dement (Amst), 2017)
INTRODUCTION: The association between age at injury (AAI) and long-term cognitive outcome of traumatic brain injuries (TBI) is debatable. METHODS: Eligible participants with a history of TBI from Alzheimer's Disease Neuroimaging Initiative were divided into a childhood TBI (cTBI) group (the AAI ≤ 21 years old) and an adult TBI (aTBI) group (the AAI > 21 years old). RESULTS: The cTBI group has a higher Everyday Cognition total score than the aTBI group. All perceived cognitive functions are worse for the cTBI group than for the aTBI group except memory. By contrast, the cTBI group has higher assessment scores on either the Boston Naming Test or Rey Auditory Verbal Learning Test than the aTBI group. DISCUSSION: The AAI is associated with the long-term cognitive outcomes in older adults with a history of TBI.